Suitability of Nondestructive Testing of Asphalt Concrete for Detecting the Impact of Moisture Damage - Saad Issa Sarsam (Britain International for Academic Research (BIAR) Publisher, 2021)
Asphalt pavement susceptibility to moisture damage is considered as a major issue in the durability and service life of the roadway. Quick and nondestructive testing of asphalt concrete pavement are the major concern for predicting its suitability for evaluation. In the present investigation, nondestructive test has been implemented to detect the moisture damage issue of asphalt concrete mixture. Asphalt concrete specimens were prepared using Marshall method. Aggregates gradation of wearing, binder and base course was implemented for the preparation of the specimens. Specimens were tested for ultrasonic pulse velocity before and after practicing the moisture damage procedure. The variations of seismic modulus among various gradation before and after the moisture damage were considered as a criterion for moisture damage and related to tensile strength ratio TSR. It was observed that the pulse velocity decline by a range of (11 to 16) for asphalt concrete after moisture damage. It was concluded that the Seismic modulus as calculated from the ultrasonic pulse velocity test was effective in distinguishing the impact of moisture damage. The seismic modulus at optimum asphalt content decline by (34.7, 46.7, and 52.6) % after moisture damage for wearing, binder, and base course mixtures respectively. The ultrasonic pulse velocity test is recommended for assessing the susceptibility of asphalt concrete mixture to moisture damage.